Organizational Capabilities as a Determining Factor for Sustainability: Case Study of the Socio-Environmental Management of Covid – 19 in Peru - Lastra Céspedes, Jeraldy Jeshely (2025)
Socio-environmental management becomes challenging in a period of uncertainty. On March 11, 2020, the Coronavirus was declared a global pandemic, forcing organizations to redesign their management strategies. Therefore, this article analyzed some measures to face the COVID-19 in Peru (the country with the highest mortality rate in the world) based on the design principles (characteristics of norms) and the principles of resilience (characteristics of adaptive strategies). It became evident that the measures taken by the government in charge were not appropriate, as they negatively affected the economy, the health system and accelerated the spread of the virus. This led to the weakening of organizational capabilities (skills and aptitudes to integrate technological knowledge and skills leading to a functional technical solution), moving us further away from the elusive perfect realization of sustainability. If design principles and resilience principles are properly implemented in a socio-ecological system, then organizational capabilities will bring us closer to sustainability, understanding that sustainability only makes sense if humanity continues to exist in an environment where its dignity s respected, that is, its collective participation.